Global civilization in the 21st century - Targowski, Andrew, 1937- (Focus on civilizations and cultures., 2014)
The purpose of this book is to evaluate the question: What does the New World Order (NWO) mean in the 21st century? After the Polish Revolution in 1989 and the fall of the Berlin Wall in 1989 and the Soviet Union in 1991, many people expected better times than those during the Cold War between the West and East. Since Communism lost to Capitalism, can the latter promote freedom and happiness for all of us everywhere? However, this dream did not happen, vice versa we face now so called liquid times, times of instability and chaos. Therefore, this book is written for those who would like to know.